Bioinspired mechanically interlocking holey graphene@SiO2 anode. Issue 4 (5th July 2022) - Wang, Fei; Liao, Xiaobin; Wang, Haoyu; Zhao, Yan; Mao, Jian; Truhlar, Donald G.
Abstract: Mechanically interlocking structures that can enhance adhesion at the interface and regulate the stress distribution have been widely observed in biological systems. Inspired by the biological structures in the wings of beetles, we synthesized a holey graphene@SiO2 anode with strong mechanical interlocking, characterized it electrochemically, and explained its performance by finite element analysis and density functional calculations. The mechanically interlocking structure enhances lithium‐ion (Li + ) storage by transmitting the strain from SiO2 to the holey graphene and by a mechano‐electrochemical coupling effect. The interlocking fit hinders the abscission of SiO2 and the distinctive structure reduces the stress and strain of SiO2 during (de)lithiation. The positive mechano‐electrochemical coupling effect preserves the amount of electrochemically active phase (Li x Si) during cycles and facilitates Li + diffusion. Therefore, the capacity shows only a slight attenuation after 8000 cycles (cycling stability), and the specific capacity is ~1200 mA h g −1 at 5 A/g (rate‐performance). This study furnishes a novel way to design high‐performance Li + /Na + /K + /Al 3+ anodes with large volume expansion. Abstract : Inspired by the biological structure in the wings of beetles, the holey graphene@SiO2 anode with strong mechanical interlocking is synthesized. The structure enhances lithium‐ion (Li + ) storage by transmitting the strain from SiO2 to the holey graphene and by a mechano‐electrochemical coupling effect. The interlocking fit hinders the abscission of SiO2 .